OCULAR SONOGRAM OF INDONESIAN STRAY CAT EYES - Ulum, Mokhamad Fakhrul; Noviana, Deni (Buletin Veteriner Udayana, 2017)
The purpose of this study was to investigate Indonesian stray cat (KLI) eyes by transpalpebrae B-mode ultrasound imaging. Eight healthy adult stray cats with 3.0-4.0 kg body weight were underwent of eyes ultrasound scanning without anesthesia or sedation. Linear ultrasound transducer with 7.5-15 MHz of frequency and ultrasound-gel were adhered directly to palpebral on the closed eyes. The results showed that the internal architecture of eyes was visible in different echogenicity according to the constituent of eyes structure. The sonograms with hypoechoic to hyperechoic parts of eyes were cornea, iris, cilliary body, suspensor ligament, sclera, and lens capsule. Moreover, anechoic parts of sonograms that having aqueous constituent were anterior chamber, posterior chamber, and vitreous humor. Based on the result, it can be concluded that B-mode ultrasound was able to assess the eyes through transpalpebral scanning.